THE EFFECT OF FINANCIAL RATIO ON THE BANK PROFITABILITY IN BANKS TO LISTED IN THE INDONESIA STOCK EXCHANGE - Sri Liniarti (Institute of Computer Science (IOCS), 2021)
The objective of the research was to examine analyze the influence of financial performance ( Capital Adequacy Ratio (CAR), Net Profit Margin (NPM), Loan to Deposit Ratio (LDR) and Operating Cost against Operating Income (BOPO) to Return On Asset (ROA)) in Banking companies listed on the Indonesia Stock Exchange. This research is using Explanatory Research which Quantitative approach. The sampling technique used was purposive sampling in which banking companies were listed on the Indonesia Stock Exchange in the period 2017-2019. In which for the 3 years observations period. The population observed is 10 banking companies with the samples are 30. The analysis was by using, multiple linear regression analysis. The result shows that simultaneously, financial performance ( Capital Adequacy Ratio (CAR), Net Profit Margin (NPM), Loan to Deposit Ratio (LDR), Operating Cost against Operating Income (BOPO) influenced Return On Asset (ROA). But partially, Capital Adequacy Ratio (CAR) is not significant effect on Return On Asset (ROA). with the samples are 30. The analysis was by using, multiple linear regression analysis. The result shows that simultaneously, financial performance Capital Adequacy Ratio (CAR), Net Profit Margin (NPM), Loan to Deposit Ratio (LDR), Operating Cost against Operating Income (BOPO) influenced Return On Asset (ROA). But partially, Capital Adequacy Ratio (CAR) is not significant effect on Return On Asset (ROA).